2009
DOI: 10.1186/cc7980
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of bacterial NOD2 agonist and its link with inflammation

Abstract: Introduction The gut is often considered as the motor of critical illness through bacterial translocation, which amplifies the inflammatory response and alters the immune status. However, systemic bacterial translocation was rarely proven and endotoxin measurement only reflects translocation of Gramnegative-derived products. The process could be more frequently identified if peptidoglycan, derived from both Gramnegative and Gram-positive bacteria, was measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 46 publications
(56 reference statements)
3
14
0
Order By: Relevance
“…These observations were in agreement with an earlier finding that systemic activation of the innate immune system by the gut microbiota involves recognition of meso-diaminopimelic acid (mesoDAP)-containing peptidoglycan found predominantly in Gram-negative bacteria, by the pattern recognition receptor nucleotide-binding, oligomerization domain-containing protein-1 (Nod1) [73]. Similarly abdominal surgery causes systemic release of Nod2-binding bacterial components and consequent rises in several inflammatory biomarkers [74].…”
Section: Regulation Of Innate Immunitysupporting
confidence: 92%
“…These observations were in agreement with an earlier finding that systemic activation of the innate immune system by the gut microbiota involves recognition of meso-diaminopimelic acid (mesoDAP)-containing peptidoglycan found predominantly in Gram-negative bacteria, by the pattern recognition receptor nucleotide-binding, oligomerization domain-containing protein-1 (Nod1) [73]. Similarly abdominal surgery causes systemic release of Nod2-binding bacterial components and consequent rises in several inflammatory biomarkers [74].…”
Section: Regulation Of Innate Immunitysupporting
confidence: 92%
“…The stimulation of PRRs by the microbiota in the intestine promote local innate defenses to bacterial infection at this site (17), and PRR ligands restore defective adaptive immunity to viral infection in the lung after microbiota depletion (33). Previous work also has shown that bacterial PRR ligands from the commensal microbiota are present in the circulation of normal healthy mice and humans (34,49,50). These PRR ligands bathe nonmucosal tissues and can enhance the antibacterial activity of bone marrow-derived neutrophils in ex vivo killing assays (34).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to TLRs, whose activation is tightly restrained in the intestine (65), NLRs are expressed in the intestinal mucosa and are activated by resident commensals (66), and this could result in the production of a signal originating from the intestinal mucosa that has a systemic effect on host lung function. Alternatively, peptidoglycan from the intestinal microbiota is found systemically in nonmucosal tissues of healthy mice and humans (including blood, spleen, and bone marrow) (34,49,50), and this disseminated peptidoglycan may activate underlying lung tissue to regulate alveolar macrophage function.…”
Section: Discussionmentioning
confidence: 99%
“…They mediate activation of mitogen-activated protein kinases and NF-JB through a CARD-dependent recruitment of RIP2. 9,19,20 Kim et al 21 suggest that the presence of NOD2 agonist also contributes to the inflammatory response. In vitro, NOD2 has been found involved in the bacterial clearance of Salmonella and Streptococcus species.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that NOD2 is mainly expressed in antigen-presenting cells and epithelial cells. 21 Because PWBCs contain a large number of antigenpresenting cells such as dendritic cells and macrophages, 26,27 it is not surprising that a higher level of NOD2 was detected in PWBCs. In the pancreatic tissue directly exposed to inflammatory bacteria in the AP rats, NOD2 was found to be expressed at a relatively lower level.…”
Section: Discussionmentioning
confidence: 99%